O valor da expressão (√3 cos x)/((sen x)/2) - (tg x)/√3 quando x=π/3 é:
Soluções para a tarefa
Respondido por
0
(√3 cos x)/((sen x)/2) - (tg x)/√3 para x = π/3
sen(π/3) = √3/2
cos(π/3) = 1/2
tg(π/3) = √3
Portanto fica assim:
(√3 cos π/3)
----------------- - (tg π/3)/√3 =
((sen π/3)/2)
√3/2
------------ - (tg π/3)/√3 =
(√3/2)/2
√3/2
---------- - √3/√3 =
√3/4
(√3/2) . (4/√3) - 1 =
2 - 1 = 1
O valor da expressão é 1
*-*-*-*-*-*-*-*-*-*-*-*
02/05/2017
Sepauto
SSRC
*-*-*-*-*-*-*-*-*-*-*-*
sen(π/3) = √3/2
cos(π/3) = 1/2
tg(π/3) = √3
Portanto fica assim:
(√3 cos π/3)
----------------- - (tg π/3)/√3 =
((sen π/3)/2)
√3/2
------------ - (tg π/3)/√3 =
(√3/2)/2
√3/2
---------- - √3/√3 =
√3/4
(√3/2) . (4/√3) - 1 =
2 - 1 = 1
O valor da expressão é 1
*-*-*-*-*-*-*-*-*-*-*-*
02/05/2017
Sepauto
SSRC
*-*-*-*-*-*-*-*-*-*-*-*
Perguntas interessantes
Geografia,
11 meses atrás
Matemática,
11 meses atrás
Matemática,
11 meses atrás
Biologia,
1 ano atrás
História,
1 ano atrás
História,
1 ano atrás